"Click" on Alkynylated Carbon Quantum Dots: An Efficient Surface Functionalization for Specific Biosensing and Bioimaging. Issue 9 (12th January 2017) - Gao, Ming Xuan; Yang, Lin; Zheng, Yi; Yang, Xiao Xi; Zou, Hong Yan; Han, Jing; Liu, Ze Xi; Li, Yuan Fang; Huang, Cheng Zhi
Abstract: Surface functionalization is an essential pre requisite for wide and specific applications of nanoparticles such as photoluminescent (PL) carbon quantum dots (CQDs), but it remains a major challenge. In this report, alkynylated CQDs, prepared from carboxyl‐rich CQDs through amidation with propargylamine in the presence of 1, 1′‐carbonyldiimidazole, were modified efficiently with azido molecular beacon DNA through a copper(I)‐catalyzed alkyne–azide cycloaddition reaction (CuAAC). As a proof‐of‐concept, the DNA‐modified CQDs are then bonded with gold nanoparticles (AuNPs, 5 nm) through a gold–sulfur bond. Owing to the emission enhancement, this complex can then be applied to the recognition of a single‐base‐ mismatched target. The same functionalizing strategy applied to click the alkynylated CQDs with a nuclear localization sequence (NLS) peptide showed that the NLS‐modified CQDs could target the nuclei specifically. These results indicate that surface functionalization of CQDs through a nonstoichiometric copper chalcogenide nanocrystal‐ (nsCuCNC‐) catalyzed click reaction is efficient, and has significant potential in the fields of biosensing and bioimaging. Abstract : On the dot : Alkynylated carbon quantum dots (CQDs), prepared through the amination reaction between carboxyl CQDs and propargyl amine, were covalently bonded with azido‐modified molecules through a copper(I)‐catalyzed alkyne–azide cycloaddition reaction (see figure), facilitating further surface functionalization for biosensing and bioimaging.